2019
DOI: 10.26717/bjstr.2019.23.003953
|View full text |Cite
|
Sign up to set email alerts
|

Utility of High-Resolution Ultrasonography by Using Acoustic Coupler in Dermatology

Abstract: We have described the experience using the acoustic coupler for subcutaneous angiolipoma comprehensively diagnosed in the lower extremity. The feature of ultrasonography (US) image with the acoustic coupler is more clearly depicted, particularly in superficial or near-field location. The usefulness of this procedure has been demonstrated as stableness state, equipped condition, and satisfactory observation for vasculature status due to the low attenuation material as previously described. The author will also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Recently, the study using the ultra-highfrequency ultrasound in the evaluation of pediatric pilomatricoma has been reported [11]. The author usually performs US studies for dermatologic fields with a high-resolution, broad-band (5MHz-18MHz) linear transducer (Nobulus Hitachi, Ltd.Tokyo, Japan) and described several reports in the dermatologic area [2,4,5,[12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Ultrasound In Dermatologymentioning
confidence: 99%
“…Recently, the study using the ultra-highfrequency ultrasound in the evaluation of pediatric pilomatricoma has been reported [11]. The author usually performs US studies for dermatologic fields with a high-resolution, broad-band (5MHz-18MHz) linear transducer (Nobulus Hitachi, Ltd.Tokyo, Japan) and described several reports in the dermatologic area [2,4,5,[12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Ultrasound In Dermatologymentioning
confidence: 99%
“…Recently, Yang et al [2] described that the target sign is a prominent feature on US in peripheral schwannoma. The author usually performs US studies for dermatologic fields with a high-resolution, broad-band (5MHz-18MHz) linear transducer (Nobulus Hitachi, Ltd. Tokyo, Japan) and described several studies including schwannoma [4][5][6][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Ultrasound In Dermatologymentioning
confidence: 99%
“…The author has previously described anatomy in dermatological ultrasound [16]. Klauser et al [17] suggested that red is used to represent softer tissues, blue represents harder tissues, and yellow or green represent intermediate tissue elasticity on sonoelastography.…”
Section: Normal Skin Elasticitymentioning
confidence: 99%
“…We usually perform US studies for dermatologic fields with a high-resolution, broad-band (5MHz-18MHz) linear transducer (Nobulus Hitachi, Ltd.Tokyo, Japan). We have also provided several reports of the dermatologic lesion [5][6][7][8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%